2007
DOI: 10.1007/s11121-007-0074-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Culturally Adapted Intervention for Youth Living with HIV in Uganda

Abstract: This study examined whether a culturally adapted version of a previously evaluated efficacious HIV prevention program reduced sexual risk behaviors of youth living with HIV (YLH) in Uganda. YLH, 14 to 21 years, were randomized to intervention (N=50) or control (N=50) conditions. Significantly more YLH in the intervention used condoms consistently and decreased their number of sexual partners in comparison to the control condition. Western interventions can be culturally adapted to retain efficacy in reducing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 9 publications
1
34
0
Order By: Relevance
“…The located studies evaluate all the categories of social protection: four programmes evaluated cash-only social protection, seven care-only interventions, while eleven reviewed combinations of social protection: four cash-plus-care, iii three care-plus-capability, two cash-plus-capability, and one of three categories of social protection: cash-plus-care-plus-capability. Seven studies of care-only interventions included HIV-positive children and adolescents: two pre-post pilot studies (Bhana et al, 2014; Snyder et al, 2014), two mixed methods studies (Lightfoot, Kasirye, Comulada, & Rotheram-Borus, 2007; Webster Mavhu et al, 2013), and three qualitative studies (Parker et al, 2013; Senyonyi, Underwood, Suarez, Musisi, & Grande, 2012; Willis et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…The located studies evaluate all the categories of social protection: four programmes evaluated cash-only social protection, seven care-only interventions, while eleven reviewed combinations of social protection: four cash-plus-care, iii three care-plus-capability, two cash-plus-capability, and one of three categories of social protection: cash-plus-care-plus-capability. Seven studies of care-only interventions included HIV-positive children and adolescents: two pre-post pilot studies (Bhana et al, 2014; Snyder et al, 2014), two mixed methods studies (Lightfoot, Kasirye, Comulada, & Rotheram-Borus, 2007; Webster Mavhu et al, 2013), and three qualitative studies (Parker et al, 2013; Senyonyi, Underwood, Suarez, Musisi, & Grande, 2012; Willis et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…All four experimental design studies reported within-group change for at least one sexual behaviour over time, with three randomising participants to a control and an intervention group [41,42,78]. …”
Section: Resultsmentioning
confidence: 99%
“…Three of the included intervention studies were individual-level randomised controlled trials [41,42,78] (Table 5), with one pre- and post-test experimental design study [40]. All interventions measured at least one high-risk sexual practice, with all measuring condom use or unprotected sex, three measuring number of sexual partners, and one measuring transactional sex.…”
Section: Resultsmentioning
confidence: 99%
“…Latino and African American), the relative efficacy of the intervention for different racial ethnic groups should be explored in addition to assessing the intervention with a larger sample of individuals from different cultures. Consideration of cross-cultural efficacy of HIV-prevention and risk-and stigma-reduction interventions is paramount not only for adaptation to other populations in the United States, but in a global context (Lightfoot, Kasirye, Comulada, & Rotheram-Borus, 2007). Improved capacity to measure and understand HIV-related stigma (USAID, 2006a(USAID, , 2006b) will need to be employed at a population level over time to understand the efficacy of efforts to reduce this and underlying stigmatizing attitudes (e.g.…”
Section: Discussionmentioning
confidence: 99%